Non-native zoobenthic species at the Crimean Black Sea Coast - SHALOVENKOV, N. N. (Mediterranean Marine Science, 2017)
More than 40 non-native species have been registered in the zoobenthos of the Black Sea. Only, five alien species, the Crustacea, Rhithropanopeus harrisii (Gould, 1841) and Rhithropanopeus harrisii (Gould, 1841), and the Mollusca, Rapana venosa (Valenciennes, 1846), Mya arenaria (Linne, 1758) and Anadara kagoshimensis (Tokunaga, 1906), were recorded in the benthos on the Crimean shelf between 1999-2014. The blood-cockle A. kagoshimensis had settled on many sites of the Black Sea shelf in the past forty years. The first detection (1999) at the Crimean coast and the temporal variability of this mollusc’s population coincided with the tendency in variability of the water temperature in the area. The five alien species had spatial aggregation and their occurrence did not exceed 23 % in the boundaries of the distribution sites. An increasing trend for their abundance in the last five - seven years was observed. These years were characterized by temperature rise in the surface layer of coastal waters. Similar patterns have been observed in the interannual variability of the biomass and abundance ratio of aliens to native for all zoobenthic taxonomic groups, i.e. of dominance index of alien species. The low level of the dominance index of the introduced species is indicative of low impact on the diversity of the benthic communities of the Crimea coast, i.e. on the scale of the metacommunity. With the exception of the R. venosa, they exhibited lower biomass and abundance along the Crimean coast shelf as opposed to other areas of the Black Sea shelf. Occasionally, the dominance index for the barnacle Amphibalanus improvisus (Darwin, 1854) could be high, a fact attributed to the low biomass and abundance of other benthic species.